Democratising the EU from below? citizenship, civil society and the public sphere - Liebert, Ulrike; Gatting, Alexander; Evas, Tatjana (Routledge, 2016)
For the European Union of the 21st century, the search for sustainable prosperity and stability includes the challenge of reconciling democratic ideals and practices with the construction of a European constitutional order. From the 2001 Laeken Summit to the 2009 Lisbon Treaty and beyond EU leaders have repeatedly set out to bring citizens closer to EU governance by making it more democratic and effective yet several national ratification referendums have shown that publics are divided about whether and why to endorse or veto complex EU reform packages imposed from the top down. Despite these limitations people do effectively engage in the making of a European polity. By initiating national court proceedings active citizens are promoting fundamental European rights in Member States' practices. As party members they contribute to shaping mass media communication about, and national publics' understanding of, European political alternatives. As civil society activists citizens help build social networks for contesting certain EU reforms or advocating others. Last but not least, as voters in national and European elections they choose between competing party visions, and national parliamentary stances regarding the role of democratic citizenship. This original contribution to the debate about democratic citizenship vis-à-vis the challenges of economic globalization and European political integration presents critical explorations of different fields of direct, representative, participatory and deliberative democratic citizenship practices that affect the transformation of Europe.